The dynamic crack propagation behavior of mode I interlaminar crack in unidirectional carbon/epoxy composites. (15th June 2019) - Liu, Huifang; Meng, Xianghao; Zhang, Huawen; Nie, Hailiang; Zhang, Chao; Li, Yulong
Graphical abstract: Highlight: Dynamic pure mode I interlaminar fracture was achieved in double cantilever beam (DCB) specimens. The crack propagation toughness was determined using the hybrid experimental-numerical method. External loading and stress waves emitting from the crack tip affect the behavior of the dynamic crack. The dynamic propagation toughness is not a single-valued function of the crack velocity for mode I interlaminar fracture. Abstract: The dynamic propagation behavior of the mode I interlaminar crack in unidirectional carbon/epoxy composites was investigated by using double cantilever beam (DCB) specimens. The dynamic interlaminar propagation toughness was obtained using a hybrid experimental-numerical method. Using a novel electromagnetic Hopkinson bar system, pure mode I fracture was guaranteed by symmetrical opening displacement rates in the range of 10 – 30 m/s. The crack velocities before crack arrest were between 100 and 250 m/s, which was monitored by crack-propagation gauges and high-speed photography. To model the interlaminar crack, a user-defined cohesive element was developed, which integrated the experimentally measured crack propagation history. The propagation toughness was calculated by the energy balance method and the dynamic J-integral technique. Results from extensive studies indicate that the dynamic propagation toughness is not a single-valued function of the crack velocity for mode I interlaminar crack. Both the external dynamic loads and the interaction with the bending waves emanating from the moving crack tip affect the behavior of the crack propagation.